2019
DOI: 10.1162/adev_a_00124
|View full text |Cite
|
Sign up to set email alerts
|

Labor Market Returns to Education and English Language Skills in the People's Republic of China: An Update

Abstract: We reexamine the economic returns to education in the People's Republic of China (PRC) using data from the Chinese General Social Survey 2010. We find that the conventional ordinary least squares estimate of wage returns to schooling is 7.8%, while the instrumental variable estimate is 20.9%. The gains from schooling rise sharply with higher levels of education. The estimated returns are 12.2% in urban provinces and 10.7% in coastal provinces, higher than in rural and inland areas. In addition, the wage premiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 112 publications
0
4
0
Order By: Relevance
“…Gazzola and Mazzacani (2019) show that English language skills increase the probability of being employed for men in Germany, Italy and Spain and women in Germany and Italy, although French language skills have no significant impact. Asadullah and Xiao (2019) show that English language skills bring a wage premium in China. Foreman-Peck and Zhou (2015) study small and medium-size exporting firms in Europe and show the lack of investment in language skills in English native speaking countries.…”
Section: Related Literaturementioning
confidence: 99%
“…Gazzola and Mazzacani (2019) show that English language skills increase the probability of being employed for men in Germany, Italy and Spain and women in Germany and Italy, although French language skills have no significant impact. Asadullah and Xiao (2019) show that English language skills bring a wage premium in China. Foreman-Peck and Zhou (2015) study small and medium-size exporting firms in Europe and show the lack of investment in language skills in English native speaking countries.…”
Section: Related Literaturementioning
confidence: 99%
“…At the same time, they are more ready to move elsewhere. To retain such individuals, and to avoid high employee turnover rates that lead to unstable working arrangements, loss of valuable experiences, and difficulty in replacing highly educated migrants who have foreign language skills, employers are more likely to pay higher wages (Asadullah & Xiao, 2019). Therefore, we hypothesize that,H2 Highly educated migrants without local hukou who know a foreign language have the highest returns on their human capital in comparison to migrants with local hukou and local‐born workers who know a foreign language.…”
Section: The Chinese Context and Hypothesesmentioning
confidence: 99%
“…Accordingly, this paper mainly discusses two scenarios representing China's typical migration patterns: inland-coastal migration (scenario 1) and coastal-inland migration (scenario 2). In the meantime, scholars have also identified that coastal developed regions have a higher skill premium of wage (or return to skills) than inland regions (Asadullah & Xiao, 2019Whalley & Xing, 2014;Zou et al, 2009). Therefore, we can assume that return to skills (η) in coastal regions is higher than that in inland regions.…”
Section: Theoretical Analysis Of Selection Patternmentioning
confidence: 99%